A Clinical Case Study On The Ayurvedic Management Of Pandu Roga (Anaemia) - Dhakad, Rita; Gowswami, Babita; Prasad, Mahendra (International Research Journal of Ayurveda & Yoga, 2021)
Pandu Roga can be closely correlated with anaemia in modern science. This disease causes a reduction often in red blood cells (RBCs) and Haemoglobin. A Prominent diagnostic feature of Pandu Roga (Anemia) is hemoglobin estimation. The assessment was Panduta (pallor of skin), Karnachhweda (tinnitus), Hatanala (loss of appetite), Shwasa (breathlessness), Bhrama (vertigo), Gatrashoola (bodyache) and Hrid-drava (palpitation). A 38 years female lady having complaint of Panduta (Pallor of skin),Aruchi (loss of appetite), Daurbalya (weakness), Pindikodweshtana (leg cramps), Akshikutshotha (periorbital oedema), Shrama (fatigue), Shwasa (breathlessness) and Hridspandnam (palpitation) and hemoglobin concentration was 4.7 gm% comes in the OPD. The subjective assessment was done with 0, 1, 2 and 3 grading of questionnaires containing specific questions. The patient was advised to Lohasava, Liver tonic, Punanarnava Mandur and Arogyavardhani Vati twice for three months and followed-up of 15 days interval, there is improvement in clinical symptoms and Hemoglobin 5.7 gm%, 10.2gm% and 13.2 gm% at different follow-up study.